Emergent Differential Organization of Airway Smooth Muscle Cells on Concave and Convex Tubular Surface - Jin, Yang; Liu, Lei; Yu, Peili; Lin, Feng; Shi, Xiaohao; Guo, Jia; Che, Bo; Duan, Yiyuan; Li, Jingjing; Pan, Yan; Luo, Mingzhi; Deng, Linhong (Frontiers in Molecular Biosciences, 2021)
Airway smooth muscle cells (ASMCs) exist in a form of helical winding bundles within the bronchial airway wall. Such tubular tissue provides cells with considerable curvature as a physical constraint, which is widely thought as an important determinant of cell behaviors. However, this process is difficult to mimic in the conventional planar cell culture system. Here, we report a method to develop chips with cell-scale tubular (concave and convex) surfaces from fused deposition modeling 3D printing to explore how ASMCs adapt to the cylindrical curvature for morphogenesis and function. Results showed that ASMCs self-organized into two distinctively different patterns of orientation on the concave and convex surfaces, eventually aligning either invariably perpendicular to the cylinder axis on the concave surface or curvature-dependently angled on the convex surface. Such orientation alignment of the ASMCs were maintained even when the cells were in dynamic movement during migration and spreading along the tubular surfaces. Furthermore, the ASMCs underwent a phenotype transition on the tubular (both concave and convex) surfaces, significantly reducing contractility as compared to ASMCs cultured on flat surface, which was reflected in the changes of proliferation, migration and gene expression of contractile biomarkers. Taken together, our study revealed a curvature-induced pattern formation and functional modulation of ASMCs in vitro, which is not only important to better understanding airway smooth muscle pathophysiology, but may also be useful in the development of new techniques for airway disease diagnosis and therapy such as engineering airway tissues or organoids.